2014
DOI: 10.1007/s10143-014-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery for tumors of the pineal region via a paramedian infratentorial supracerebellar keyhole approach (PISKA)

Abstract: The tumors of the pineal region represent a significant challenge in terms of patient selection and surgical approach. Traditional surgical options were commonly used to approach this area causing considerable surgical morbidity and mortality. We report for the first time on a series of endoscopic procedures for lesions of the pineal region performed via an infratentorial supracerebellar keyhole approach (PISKA) in the prone position using endoscope-assisted and endoscope-controlled technique. A single-institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…Patients with benign Fig. 1 Representative case with a pineal lesion resected endoscopically [33]. A 14-year-old girl presented with headache and double vision.…”
Section: Follow-upmentioning
confidence: 98%
“…Patients with benign Fig. 1 Representative case with a pineal lesion resected endoscopically [33]. A 14-year-old girl presented with headache and double vision.…”
Section: Follow-upmentioning
confidence: 98%
“…32 Most studies of endoscopic surgeries for thalamic lesions are limited to the anterior part of the thalamus 36 or endoscopic biopsy, 1,33 but none have focused on the pulvinar. Tseng et al 41 performed an endoscopic supracerebellar infratentorial retropineal approach, and Thaher et al 40 performed a paramedian infratemporal supracerebellar key approach to pineal gland tumors close to the pulvinar. These approaches are likely suitable for lesions in the pulvinar as well.…”
Section: Discussionmentioning
confidence: 99%
“…[71] Multiple studies [65,66,72,73] have demonstrated ETV's safety, diagnostic efficacy, and lower morbidity and mortality compared with conventional approaches. Recently, Thaher et al [74] also reported 11 cases of endoscopic surgery via a paramedian infratentorial supracerebellar keyhole approach (PISKA) for tumors of the pineal region. They believed that the endoscopically PISKA is a safe and effective minimally invasive approach that enables endoscopic treatment of different lesions in the pineal region, accompanied with comparable results to standard microsurgical technique but with less morbidity.…”
Section: Surgical Management Of Suspected Igcts: Endoscopic or Open Smentioning
confidence: 95%